Entropy-driven difference in interfacial water reactivity between slab and nanodroplet - Shiwei Chen; Jiabao Zhu; Jifan Li; Pan Guo; Jinrong Yang; Xiao He (Nature Communications)
Abstract Interfacial water activity plays a critical role in governing chemical reactivity and catalytic efficiency, yet a quantitative understanding of how hydrogen-bond (H-bond) network structure influences this reactivity remains limited. Herein, we employ ab initio molecular metadynamics simulations to delineate the relationship between the H-bond network and the reactivity of interfacial water molecules at the slab and nanodroplet systems. Interfacial water at nanodroplets, characterized by microscopic inhomogeneity, tends to adopt a donor–acceptor dimer configuration, in contrast to the more homogeneous H-bond network at the slab. This disparity in local structure, corroborated by the quantified differences in solvation configurational entropy, results in a reduction of the reaction free energy barrier by 1–2 kcal·mol⁻1 at the slab interface, corresponding to an order-of-magnitude enhancement in reaction rate. These results provide a fresh perspective to understand the interfacial water reactivity and highlight the critical role of H-bond network in optimizing catalytic performance.